Lethal Attack on Lethal Injection: A Proposal to End the Final Loophole in the Death Penalty Debate - Jasmine Sharma (Washington University Journal of Law & Policy, 2019)
This note addresses the current state of lethal injection in the American criminal justice system, especially the actions of individual states aiming to perpetuate this practice. The note first reviews the history of this method of execution, including why it initially came into favor during the 20th century, and relevant legal developments supporting its continued use. The focus of the note is on the results of recent attempts by corporations and foreign countries to disrupt supplies of the necessary drugs, as they consider their use in execution to be unethical. Against this backdrop, states have sought other methods for obtaining the necessary drugs to continue to perform lethal injection, including compounding pharmacies. For both ethical and practical reasons, the note proposes an end to this practice, via increased regulation of compounding pharmacies.
Keywords: death penalty; lethal injection; criminal justice; execution; compounding pharmacies